2017
DOI: 10.15761/jsin.1000173
|View full text |Cite
|
Sign up to set email alerts
|

Self-government of complex reading and writing brains informed by cingulo-opercular network for adaptive control and working memory components for language learning

Abstract: To understand mental self-government of the developing reading and writing brain, correlations of clustering coefficients on fMRI reading or writing tasks with BASC 2 Adaptivity ratings (time 1 only) or working memory components (time 1 before and time 2 after instruction previously shown to improve achievement and change magnitude of fMRI connectivity) were investigated in 39 students in grades 4 to 9 who varied along a continuum of reading and writing skills. A Philips 3T scanner measured connectivity during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Taken together, RD readers show a significant increase in phonological reading at the Moreover, the catch-up at the left IFG seems to be driven by over-connectivity with other brain regions especially in the right hemisphere in adults with RD (Yan et al, under review). Previous studies have suggested that strong connection with other parts of the brain helps to normalize brain function of the left IFG (Richards et al, 2018). Additionally, it was also found that there is a lack of developmental increase in task specialization in RD readers (Yan et al, under review).…”
Section: Brain Changes Underlying Reading Development In Rdmentioning
confidence: 99%
“…Taken together, RD readers show a significant increase in phonological reading at the Moreover, the catch-up at the left IFG seems to be driven by over-connectivity with other brain regions especially in the right hemisphere in adults with RD (Yan et al, under review). Previous studies have suggested that strong connection with other parts of the brain helps to normalize brain function of the left IFG (Richards et al, 2018). Additionally, it was also found that there is a lack of developmental increase in task specialization in RD readers (Yan et al, under review).…”
Section: Brain Changes Underlying Reading Development In Rdmentioning
confidence: 99%
“…Likewise, children produce letters through their hands to spell written words and compose sentences and text about what they read or hear. Also motor functions are involved in the eye movements as they read written words in the context of sentences, either orally or silently (Yagle et al, 2017).…”
Section: Study 2: Relationships Of Brain's Motor Functions and Pathways With Language Systemsmentioning
confidence: 99%
“…Attention and executive functions. : Attention and executive functions are relevant to learning from teacher talk during oral instruction (Berninger, Abbott, Cook, and Nagy, 2017) as well as the learner's self-regulation of the learning process (e.g., Richards et al, 2017). Examination of the content of compositions in a cross-sectional study grades 1 to 9 (see Berninger, 2009) showed that students in general education wrote more about relationships with other students, the teacher, or family issues.…”
Section: Multiple Motor Domainsmentioning
confidence: 99%